Effects of low frequency on polymer mixed concrete / Haszeme Abu Kasim ... [et al.] - Abu Kasim, Haszeme; Sukarman, Firdaus; Rusli, Ahmad Najmie; Khodori, Ahmad Faidzal; Ismail, Ainaa Maya Munira (2017)
In recent years, it has been found that some concrete structures, even for some high performance concrete and ready mixed concrete under good quality control, start to deteriorate long before reaching their designed service life. In this paper, the main objective of this research is to study the effect of fiber on to the fatigue strength of the polymer-mixed concrete. The polymer concrete that has been used in this study is a series formulation with ratio of 60:30:10 of sand, polyester resin and talcum powder. For a fiber-reinforced polymer concrete, chopped strand mat glass fiber is added 0.25% by weight of mixture and reducing the sand by 59.75% from above ratio. Polymer-mixed concrete with and without fiber were tested with tensile and fatigue. In fatigue test, three points bend specimen with and without notch were employed. The tests were conducted at constant R- ratio = 0.1 and low frequency at 5 Hz.